(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2024)
The article examines the role of movies and cartoons as effective tools for learning English. It discusses how these media provide natural language contexts, promote cultural understanding, and make the learning process more engaging. Key psychological and pedagogical aspects are explored, such as passive and active learning, multimodal engagement, and the emotional impact of interesting content on language acquisition. The article concludes with recommendations for integrating movies and cartoons into language learning to enhance students’ linguistic and cultural competencies while keeping them motivated.